Kinship in Roman-Italian Relationships: Diverse Traditions, Perspectives and Interpretations in Velleius Paterculus and Other Roman and Greek Historical Writers - Russo, Federico (Histos, 2012)
This paper studies the concept of kinship between Italians and Romans in Velleius Paterculus and other historical writers, both Roman and Greek. The results have both historiographical significance, illuminating the historical writers’ varied treatments of the concept and, in some cases, the familial and ethnic influences upon them, and historical significance, allowing considered historical judgments about when and how the concept was used by Italians, including Latins, and how Romans, both corporately and individually, responded to these Italian uses. In studying the important concept of kinship, I am, of course, not claiming that it trumps other historical factors (Realpolitik considerations, for instance). In restricting the literary evidence to historical prose writers (whether historiographers, biographers, antiquarians, or orators treating historical matters), I am operating within the brief of Histos; focusing on concrete historical contexts; and leaving open the possibility that the picture might be somewhat modified if the evidence of poetry (for example, Virgil’s Aeneid or Silius’ Punica) were included.